Ammonia loss and fertilizer 15N recovery in no‐till winter wheat following BROADCAST UREA APPLICATIONS. Issue 4 (6th July 2017) - Engel, Richard; Romero, Carlos; Jones, Clain
Abstract : Broadcast applications of urea during the overwinter period has been a common management practice for dryland winter wheat producers in Montana. Their long‐held belief was that ammonia (NH3 ) volatilization risks associated with surface application of urea loss could be mitigated by applying urea to cold soils during this time. Does research support this belief? Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/495